Greed that Occurs in Kingdom of the Planet of the Apes Movie - Tita Keisya Amanda; Putri Wulandari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this study is to analyze the portrayal of greed and power in the film Planet of the Apes and focus on how these themes affect the relationship between humans and apes. This study will focus on understanding the role of greed and power in social and interspecies dynamics and explore how these destructive forces shape character behavior as well as the broader conflict in the story. This study uses qualitative descriptive analysis to explore the themes of